The Correlation Level of Stress at the Start of Pandemic Covid-19 Related to the Frequency of Relapse in Coronary Heart Disease Patients: The Correlation Level of Stress at the Start of Pandemic Covid-19 (Jurnal Ilmiah Wijaya, 2019)
Background: Respiratory syndrome of coronavirus 2 (SARS-CoV-2) causing (COVID-19) disease that has reached pandemic levels. Patients who have coronary heart disease have been identified as highly increased morbidity and mortality while suffering from COVID-19. In addition, patients with coronary heart disease are also suffering with stress. Usually, stress can cause the body to release hormones that can impact your heart to beat faster. Methodology: The design of this research used cross-sectional design which consists of Perceived Stress Scale (PSS-10). This cross sectional study employed instrument on the independent variable and one-question questionnaire on the dependent variable. This research was conducted to determine the correlation of level of stress during the pandemic COVID-19 related through the frequency of relapse in coronary heart disease patients at Indonesian Red Cross Hospital Bogor. Moreover, the research samples in this study are 33 coronary heart disease patients. Then, the data analysis techniques used univariate and bivariate analysis was studied within test statistic through Kendall’s tau. Conclusion: In conclusion, the research results showed that 33 respondents reported 28 (84.8.8%) respondents with moderate covid-19 pandemic stress levels, and there are 17 (51.5%) experienced moderate recurrence. Based on the results of cross tabulation, the data were obtained from 33 respondents there are 17 (51.5%) respondents with moderate stress levels for the COVID-19 pandemic and moderate recurrence frequency. In conclusion, the results of statistical tests obtained that p value 0.006 (p value <0.05), which means that Ha is accepted and Ho is rejected. So that, these research results highlight the serious acute impact of stress level during COVID-19 pandemic and the frequency of recurrence in coronary heart disease patients.